Construction, operations, and performance of the CMS phase-1 silicon pixel detector. (1st October 2022) - Choudhury, S.; ,
Abstract: The CMS phase-1 pixel detector was designed to cope with an instantaneous luminosity of 2 × 10 34 cm −2 s −1 and 25 ns bunch spacing with very small efficiency loss. The upgraded detector has 124 million channels that features a 4-hit coverage in the tracking volume with an additional layer in the barrel and one extra disk in both the endcaps. DC-DC converters have been used to deliver more power to the detector without the need of replacing the cable plant. A CO2 based cooling system was implemented and carbon fibre based support structures were used to reduce the material budget in the tracking volume. The data acquisition system was upgraded to cope with higher collision rates with a digital data format from the detector front-ends. The detector was installed in early 2017 and has been successfully operated since then. In this paper, the design and construction, operational experience and the performance of the phase-1 pixel detector at LHC Run 2 will be summarised.